Qualitative study: exploration of blood donation awareness among non-blood donors - Mohd Asmawi, Ummi Mohlisi; Osman, Maznah; Said, Norimah; Mohammad, Mariam (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Donating blood is a humanitarian act with lifesaving implications. Blood transfusion saves lives and helps recover many patients, as every blood component is beneficial. The general public is urged to respond to the call of blood banks to donate blood to enable them to maintain a continuous supply of blood for the vital use of patients nationwide. This study explores the level of blood donation awareness amongst non-donors and the factors that hinder them from voluntarily donating blood. Four focus group discussions (FGD) were conducted among non- blood donors. The discussions were held in separate, closed rooms. All of the sessions were recorded with the participants' permission. The discussions were conducted in the local language, and the verbatim was later translated into English. Most non-donor participants professed an awareness of the importance of donating blood to save an ill person. However, those with daily work commitments do not voluntarily donate blood mainly due to the lack of donation, such as it causing weakness and a variety of health problems. Fear is also a common factor stated by the participants, including fear of the needle, fear of blood, or a general fear of the whole blood donation process. Concerning creating awareness, some participants recommended using short films/videos or advertisements that could stir an emotional reaction. Other hindering factors are related to the common myths, fears and superstitions about blood on voluntary blood donation campaigns that were very limited. Findings indicate a need for comprehensive strategies to address these barriers and promote voluntary blood donation